Nio inc. equity research. The next generation of smart vehicles - Pocinho, Joaquim Dias (2022)
In order to have a clear vision of the future of mobility, a qualitative and quantitative assessment on NIO stoc kwere performed. Our model recommends a BUY strategy based upon three major pillars: 1) the electrification of the industry, 2) innovative charging solutions and 3) disruptive autonomous driving systems developments.